Observing Hakka’s Culture According to Hakka’s Proverbs - Sugiarto Lim (Humaniora, 2013)
Proverbs in Hakka dialect reflect the attitude of the Hakka’s social life and nature. Hakka dialect’s proverbs are divided into two major categories of social life and natural phenomenon. This article tries to analyze how is the Hakkanese culture reflected by the characteristics of these two aspects. In aspects of social life, it could be seen the proverbs from several points of view, including the religion and traditional virtue, fame and academic, regional dialects, and feng shui.  On the part of natural phenomenon, it could be seen Hakkanese dependency and understanding on the nature, as well as their agricultural production –based on their way of life and survival. The article is particularly concerned about the cultural characteristics of the Hakkanese which is shaped and reflected due to their migration history and root.